Floristic and phytogeographical affinities of the vegetation in the municipality of San José Iturbide, Guanajuato, Mexico - Gutiérrez, Jorge; Solano, Eloy (Instituto de Ecología, A.C., 2014)
A floristic study was carried out in the municipality of San José Iturbide, Guanajuato, located on the Mexican Plateau. The geographic distribution and ecological patterns of the vascular flora were analyzed. The studied area covers 538 km2. We recordered 661 species, belonging to 101 families and 301 genera. In this area two new records for the flora of Guanajuato were found, Osmunda regalis var.spectabilis and Anoda pentaschista. The floristic inventory represents around 70% of the taxa present in the zone. 41% of the species are endemic to Mexico, 114 are unique for Central Mexico, seven of these species are only distributed in areas situated near the municipality and one of them is endemic of it. The vascular flora of San José Iturbide shows geographical affinities with that of the semiarid scrubs of Central Mexico, and it shares many species with the arid climate vegetation of the Mexican Plateau. San José Iturbide contains 12% of the 5500 species estimated for the region of the project “Flora del Bajío y de Regiones Adyacentes” and 22% for the state of Guanajuato. Therefore, the floristic richness of the area is considered high, taking into account its small area.